Subtractive Gene Cloning Using Dynabeads Oligo(dT)25 for Elucidation of Pseudohyphal Formation in Candida tropicalis - Iwaguchi, Shin-Ichi; Suzuki, Takahito; Kamihara, Teijiro; Nishimura, Kazuko; Yokoyama, Koji; Imanishi, Yumi; Kawai, Toshiko (Nihon Ishinkin Gakkai zasshi, 2001)
The dimorphic transition from yeast to pseudohyphae in Candida tropicalis occurs following the addition of ethanol to a synthetic medium containing glucose. We developed a method of subtractive gene cloning to isolate genes, of which the expression was apparently specific for pseudohyphal formation in this organism. Subtraction was performed between sense-strand cDNAs instead of mRNAs from cells of the ethanol culture and anti-sense cDNAs linking to Dynabeads oligo(dT)25 from those of the control culture. Dynabeads oligo(dT)25 are paramagnetic beads with 25 nucleotide-long chains of deoxythymidines covalently linked to their surface and were expected to be easily collected using a magnet. This method using Dynabeads oligo(dT)25 minimizes the degradation of mRNA and makes it easy to construct a cDNA library sufficient to analyze the genetic information on the yeast-to-hyphae transition. Using this strategy, we identified several genes including a homologue of CPP1 coding tyrosine phosphatase and a homologue of nmt1+ encoding protein, which was reported to regulate thiamine biosynthesis.